2021
DOI: 10.1063/5.0037867
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-kinetic explosions: Safety first or safety last?

Abstract: Gas and vapour explosions have been involved in industrial accidents since the beginnings of industry. A century ago, at 11:55 am on Friday 24th September 1920, the petroleum barge Warwick exploded in London's docklands and seven men were killed. Understanding what happened when it blew up as it was being refurbished, and how to prevent similar explosions, involves chemistry plus fluid mechanics. I recount the 1920 accident as an example, together with the history of thermo-kinetic explosions prior to 1920 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The LTC and two stage ignitions, transition from a cool flame ignition to a hot flame ignition, have been studied for fire and explosion prevention in aircraft fuel tanks because the conditions in aircraft fuel tanks, that are exposed to high temperatures and low pressures due to their high altitude, may cause ignition in the fuel tanks by cool flame chemistry, hot flame chemistry, and/or two stage ignition chemistry [14,15]. An investigation into the explosion of Flight TWA in 1996, which claimed more than 200 lives, also concluded that a cool flame could be one of the possible ignition sources [16,17].…”
mentioning
confidence: 99%
“…The LTC and two stage ignitions, transition from a cool flame ignition to a hot flame ignition, have been studied for fire and explosion prevention in aircraft fuel tanks because the conditions in aircraft fuel tanks, that are exposed to high temperatures and low pressures due to their high altitude, may cause ignition in the fuel tanks by cool flame chemistry, hot flame chemistry, and/or two stage ignition chemistry [14,15]. An investigation into the explosion of Flight TWA in 1996, which claimed more than 200 lives, also concluded that a cool flame could be one of the possible ignition sources [16,17].…”
mentioning
confidence: 99%